Overcoming the Early‐stage Conundrum of Digital Platform Ecosystem Emergence: A Problem‐Solving Perspective. (12th August 2021) - Murthy, Ramya K.; Madhok, Anoop
Abstract: Platform sponsors and complementors co‐create value in digital platform ecosystems. But how does a digital platform ecosystem emerge in the incipient stage, especially in a situation where value co‐creation involves attracting complementors to platform sponsors who are unknown to one another? We posit that a platform sponsor's choice of scope signals value co‐creation opportunities and thereby attracts complementors and consumers. We draw upon the problem‐solving perspective, rooted in the knowledge‐based view of the firm, to shift the emphasis away from the actor ('who') to the problem at hand ('what') and demonstrate how incipient platform sponsors can align their scope with the problem to stimulate ecosystem emergence. Using fuzzy‐set qualitative comparative analysis on a dataset of crowdfunding campaigns, we identify multiple pathways and associated propositions for successful emergence of digital platform ecosystems, notably for innovation, open‐source, and information ecosystems. The framework we conceptualize highlights novel considerations to overcome the early‐stage challenge of attracting participation to an ecosystem that is yet to emerge.